Women’s opinions about stress during a visit to the gynaecologist’s office - Niziurski, Piotr (Medical Studies/Studia Medyczne, 2016)
Introduction: According to the guidelines of Royal College of Obstetricians and Gynaecologists gynaecological treatment (including the treatment with a speculum and bimanual treatment and test nipple) is one of the most intimate medical procedures that in many women can cause a feeling of shame and embarrassment. At the same time, in some patients, the study calls so considerable discomfort, anger and embarrassment and even if they don’t tell, they may experience prolonged stress resulting from the unpleasant and traumatic experience. Aim of the research: To investigate the opinions of women about the stress associated with their visit to the gynaecologist’s. Material and methods: The study included 331 anonymous, non-pregnant, randomly selected women. The respondents were divided into three age groups: the first group were women aged 29 years and below, the second group aged 30–39, and the third group aged 40 years and above. The study was conducted in the author’s private gynaecological office and in the Faculty of Health Sciences at the University of Jan Kochanowski in Kielce. The measurement tool was a survey of his own authorship. Results and conclusions: The greatest stress associated with gynaecological examination accompanied the woman aged 29 years and below, and the smallest at the age of 40 years and over (respectively, 46% and 35%). For most women, the gender of the gynaecologist does not matter when choosing a doctor. The opinion of the studied woman states that the most embarrassing moment of a visits at the gynaecologist is sitting down on the specialist chair and the gynaecological treatment, whereas the highest stress is evoked by the palpation through the anus and vagina. The frequency of reporting for a gynaecological examination decreases with the women’s age. Most women during the gynaecological treatment visit feel safe when alone with the doctor. Women expect the gynaecologist to be nice, talkative, and calm. When choosing a gynaecologist, patients usually guide themselves by the opinion of other women.